Ornamental potential of ferns and lycophytes in Eastern of Maranhao, Brazil (Research, Society and Development, 2020)
The identification of the ornamental potential of plants has grown in recent years, being a worldwide trend, but still underdeveloped in Brazil, where knowledge about this diversity is incipient. Ferns and lycophytes constitute a heterogeneous group, with a diversity of habitat and morphological variations that provide them with a strong ornamental potential, which is still little explored. In this context, in order to subsidize information on the ornamental and landscaping potential of pteridophytic flora, this study aimed to carry out a floristic survey of the species of ferns and lycophytes ornamental in the municipality of Caxias, Maranhão. In order to carry out this study, collections were carried out in places selling ornamental plants, leisure and wellness areas (squares and clubs), residences, hotels and hospitals in the municipality. Ferns and lycophytes cultivated as ornamentals in the municipality of Caxias/MA are represented by 21 species (19 species of ferns and two of lycophytes) distributed in 14 genera and 10 families. Of these, nine species can be found in the municipality native flora, and two are considered exotic in Brazil. The potential of this group of plants is related to the aesthetic values of their structures and adaptive plasticity, presenting characteristics suitable for ornamental and landscape use. The present research contributes in a significant way about information about the landscaping and ornamental potential of ferns and lycophytes.